Renal Tumor Cryoablation Planning. The Efficiency of Simulation on Reconstructed 3D CT Scan - Ciprian Valerian LUCAN (Applied Medical Informatics, 2010)
Introduction & Objective: Nephron-sparing surgical techniques risks are related to tumor relationships with adjacent anatomic structures. Complexity of the renal anatomy drives the interest to develop tools for 3D reconstruction and surgery simulation. The aim of the article was to assess the simulation on reconstructed 3D CT scan used for planning the cryoablation. Material & Method: A prospective randomized study was performed between Jan. 2007 and July 2009 on 27 patients who underwent retroperitoneoscopic T1a renal tumors cryoablation (RC). All patients were assessed preoperatively by CT scan, also used for 3D volume rendering. In the Gr.A, the patients underwent surgery planning by simulation on 3D CT scan. In the Gr.B., patients underwent standard RC. The two groups were compared in terms of surgical time, bleeding, postoperative drainage, analgesics requirement, hospital stay, time to socio-professional reintegration. Results: Fourteen patients underwent preoperative cryoablation planning (Gr.A) and 13 patients underwent standard CR (Gr.B). All parameters analyzed were shorter in the Gr.A. On multivariate logistic regression, only shortens of the surgical time (138.79±5.51 min. in Gr.A. vs. 140.92±5.54 min in Gr.B.) and bleeding (164.29±60.22 mL in Gr.A. vs. 215.38±100.80 mL in Gr.B.) achieved statistical significance (p<0.05). The number of cryoneedles assessed by simulation had a 92.52% accuracy when compared with those effectively used. Conclusions: Simulation of the cryoablation using reconstructed 3D CT scan improves the surgical results. The application used for simulation was able to accurately assess the number of cryoneedles required for tumor ablation, their direction and approach.